2011
DOI: 10.1021/om101171s
|View full text |Cite
|
Sign up to set email alerts
|

C−H and C−S Activations of Quinoline-Functionalized Thiophenes by Platinum Complexes

Abstract: We synthesized and characterized two ligands, 2--(quinolin-8-yl)thiophene (1a) and 3-(quinolin-8-yl)thiophene (1b). The selective C-H activation of the thiophene moieties was achieved by reacting 1a or 1b and [Pt(CH 3 ) 2 (SMe 2 )] 2 . We observed η 2thiophene intermediates during the course of the reactions. The selective C-S bond activation of the thiophene moieties was observed after reacting 1a or 1b and [Pt(dippe)H] 2 . DFT calculations were performed to elucidate the regioselectivity of C-S activations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Moreover, quinoline derivatives with the thienyl motif in other positions of the quinoline moiety are known; their synthesis has been mainly performed by modified Suzuki coupling. [36][37][38] Recently, palladium-catalyzed coupling of 2,2Ј-bithiophen-2-yl with 3-bromoquinoline to give 3-(2,2Ј-bithiophen-5-yl)quinoline was reported. [39] Herein, we report the synthesis of novel quinoline derivatives containing the 2,2Ј-bithiophen-2-yl motif through ruthenium and indium-catalyzed reactions and Suzuki coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, quinoline derivatives with the thienyl motif in other positions of the quinoline moiety are known; their synthesis has been mainly performed by modified Suzuki coupling. [36][37][38] Recently, palladium-catalyzed coupling of 2,2Ј-bithiophen-2-yl with 3-bromoquinoline to give 3-(2,2Ј-bithiophen-5-yl)quinoline was reported. [39] Herein, we report the synthesis of novel quinoline derivatives containing the 2,2Ј-bithiophen-2-yl motif through ruthenium and indium-catalyzed reactions and Suzuki coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Heptane and similar alkanes have been widely used as solvents in organometallic chemistry because they are generally inert to organometallic complexes. [6,7] Based on these considerations, the reactions of Ru 3 (CO) 12 with 1 and 2 in refluxing heptane for 24 h afforded the trinuclear ruthenium complexes (μ 3 -η 1 :η 2 :η 5 -2-phenyl-3-Cy 2 PC 9 H 4 )Ru 3 (CO) 8 (1c) and [μ-2-mesityl(3-Cy 2 PC 9 H 5 )](μ 2 -CO)Ru 3 (CO) 9 (2c) in 11 and 14% yields, , respectively, with the formation of a large amount of dark brown solid that was not soluble in common organic solvents (Scheme 2). It is confirmed that the dark brown precipitates contain Ru─H species using 1 H NMR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[5] The reactions of indenyl derivatives with Ru 3 (CO) 12 generally afford η 1 -, η 2and η 5 -indenyl ruthenium carbonyl clusters via C─H and C─P bond cleavage reactions. [6] We have recently shown that two dinuclear indenyl ruthenium clusters 1b and 2b contain an unprecedented η 3 coordination mode with bonding through the junction carbon and the adjacent carbons of the five-and six-membered rings of the indenyl ligand (Scheme 1). [7] However, other products were not well-defined in these reactions maybe because they are labile in refluxing p-xylene.…”
Section: C─h Activation Indenylphosphine Ruthenium 1 | Introductionmentioning
confidence: 99%
“…We note that '8-quinolylboronic acid' or derivatives have been utilized successfully in Suzuki coupling reactions [24,25,[27][28][29][30][31][32]. In the mechanism, boronate ions are typically invoked as solution intermediates that transfer an aryl group to Pd in a transmetalation step that ultimately leads to C-C bond formation upon reductive elimination from the Pd center.…”
Section: Resultsmentioning
confidence: 99%